Hungarian Monitoring, 25 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 25 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Embassies in Kuwait - Analysis of the situation in the Persian Gulf - Gorbachev-Dumas meeting Domestic Affairs: - Protests against the draft land law - New system of local government - Hungarian Democratic Forum (MDF) accused of purges - On the situation of the former opposition Foundation to Help the Poor - Vatra Romaenasca expects compensation from Hungary Economy: - Swine plague impact in Romania Külpolitika: - Nagykövetségek helyzete Kuvaitban - Helyzetelemzés az öbölválságról - Gorbacsov-Dumas találkozó Belpolitika: - Tiltakozások a földtörvény tervezete miatt - Új önkormányzati rendszer - Tisztogatással vádolják az MDF-et - Az egykori SZETA helyzetéről - A Vatra Românească kártérítést vár Magyarországtól Gazdaság: - A sertéspestis romániai vonatkozásai